1992
DOI: 10.1073/pnas.89.5.1745
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for IgG complexes activate synthesis of monocyte chemoattractant peptide 1 and colony-stimulating factor 1.

Abstract: The chemotactic factors responsible for complement-independent macrophage accumulation in immunecomplex diseases such as glomerulonephritis remain unknown. Fc receptors for IgG complexes are found on mesngial cells of the kidney, which produce the macrophage growth factor colony-stimulating factor 1 (CSF-1). We therefore investigated the possible stimulation of mesangial-cell expression of CSF-1 and the recently identified monocyte-specific chemoattractant protein 1 (MCP-1) by IgG complexes. IgG complexes, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…Mesangial cells play an important role in inflammation in the kidney (59,60). Interaction of ICs with mesangial cells via Fc receptors triggers a cascade of renal injury characterized by cellular proliferation, matrix protein accumulation, chemokine release, and mononuclear cell recruitment (56,(61)(62)(63)(64)(65). A recent study of lupus-prone mice (NZB/ NZW F 1 mice) deficient for Fc receptor ␥-chain I and III expression (Fc␥RI and Fc␥RIII) indicated that the presence of Fc␥Rs was required for development of proliferative glomerulonephritis (66).…”
Section: Discussionmentioning
confidence: 99%
“…Mesangial cells play an important role in inflammation in the kidney (59,60). Interaction of ICs with mesangial cells via Fc receptors triggers a cascade of renal injury characterized by cellular proliferation, matrix protein accumulation, chemokine release, and mononuclear cell recruitment (56,(61)(62)(63)(64)(65). A recent study of lupus-prone mice (NZB/ NZW F 1 mice) deficient for Fc receptor ␥-chain I and III expression (Fc␥RI and Fc␥RIII) indicated that the presence of Fc␥Rs was required for development of proliferative glomerulonephritis (66).…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic feature of GN is the infiltration of leucocytes from the circulation into the kidney tissue, and the subsequent activation of such inflammatory cells at the site of glomerular injury. It has been demonstrated that mesangial cells are a rich source of chemokines attracting different leucocyte populations into the glomerulus [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…MCs are known to take up large particles, including immune complexes (Hora et al 1992). Phagocytosis is receptor-and actin-dependent.…”
Section: Impact Of Lipid Accumulation On Phagocytosismentioning
confidence: 99%
“…MCs are known to phagocytose both particulate matter and immune complexes (Hora et al 1992), which mediate intraglomerular inflammation and limit glomerular injury. In previous short-term studies, IGF-1 treatment enhanced fluid-phase pinocytosis and membrane turnover , which would be expected to enhance phagocytosis.…”
Section: Altered Phagocytosis and Cytoskeletal Reorganizationmentioning
confidence: 99%